Knowledge, attitudes and practices towards yaws and yaws-like skin disease in Ghana - Marks, M.; Kwakye-Maclean, C.; Doherty, R.; Adwere, P.; Aziz Abdulai, A.; Duah, F.; Ohene, S.-A.; Mitja, O.; Oguti, B.; Solomon, A.W.; Mabey, D.C.W.; Adu-Sarkodie, Y.; et al. (PLoS Neglected Tropical Diseases, 2017)
Introduction: Yaws is endemic in Ghana. The World Health Organization (WHO) has launched a new global eradication campaign based on total community mass treatment with azithromycin. Achieving high coverage of mass treatment will be fundamental to the success of this new strategy; coverage is dependent, in part, on appropriate community mobilisation. An understanding of community knowledge, attitudes and practices related to yaws in Ghana and other endemic countries will be vital in designing effective community engagement strategies. Methods: A verbally administered questionnaire was administered to residents in 3 districts in the Eastern region of Ghana where a randomised trial on the treatment of yaws was being conducted. The questionnaire combined both quantitative and qualitative questions covering perceptions of the cause and mechanisms of transmission of yaws-like lesions, the providers from which individuals would seek healthcare for yaws-like lesions, and what factors were important in reaching decisions on where to seek care. Chi-square tests and logistic regression were used to assess relationships between reported knowledge, attitudes and practices, and demographic variables. Thematic analysis of qualitative data was used to identify common themes. Results: A total of 1,162 individuals participated. The majority of individuals (n = 895, 77%) reported that “germs” were the cause of yaws lesions. Overall 13% (n = 161) of respondents believed that the disease was caused by supernatural forces. Participants frequently mentioned lack of personal hygiene, irregular and inefficient bathing, and washing with dirty water as fundamental to both the cause and the prevention of yaws. A majority of individuals reported that they would want to take an antibiotic to prevent the development of yaws if they were asymptomatic (n = 689, 61.2%), but a substantial minority reported they would not want to do so. A majority of individuals (n = 839, 72.7%) reported that if they had a yaws-like skin lesion they would seek care from a doctor or nurse. Both direct and indirect costs of treatment were reported as key factors affecting where participants reported they would seek care. Discussion: This is the first study that has explored community knowledge, attitudes and practices in relation to yaws in any endemic population. The belief that ‘germs’ are in some way related to disease through a variety of transmission routes including both contact and dirty water are similar to those reported for other skin diseases in Ghana. The prominent role of private healthcare providers is an important finding of this study and suggests engagement with this sector will be important in yaws eradication efforts. Strategies to address the substantial minority of individuals who reported they would not take treatment for yaws if they were currently asymptomatic will be needed to ensure the success of yaws eradication efforts. The data collected will be of value to the Ghana Health Service and also to WHO and other partners, who are currently developing community mobilisation tools to support yaws eradication efforts worldwide. © 2017 Marks et al.
Keywords: Malaria; Malnutrition; Pregnancy; Labor and delivery; Birth weight; Nutrition; Anemia